New species of free-living marine Sabatieriinae (Nematoda: Monhysterida: Comesomatidae) from - Barnes, Natalie; Kim, Hyeong Geun; Lee, Wonchoel (Zootaxa, 2012)
Four new species from the subfamily Sabatieriinae Filipjev, 1934 are described from the south and west coast of South Korea: three new species of Laimella Cobb, 1920 and one new species of Cervonema Wieser, 1954. Two further species of Cervonema are informally described owing to the absence of male specimens. In addition, Laimella filicaudata Ward, 1974 is formally reinstated as an extant species. Sabatieriinae are relatively character poor, defined by a striate cuticle, closely spaced cephalic setae, small buccal cavity, simple arcuate spicules and precloacal supplements minute or absent. However, we have found that the de Man's ratios a, b and c, the comparable lengths of the anterior and posterior cephalic setae, the position of the amphid, shape and length of the oesophageal bulb, and the proportion of the cylindrical tail part are all species informative. Laimella ferreroi sp. nov. is most distinctive species described here, having the largest de Man's ratios a and b, the longest gubernaculum (as abd) and the longest, truly filiform, tail so far recorded in the genus. Laimella socotris sp. nov. has a distinct rounded posterior oesophageal bulb similar only to L. longicauda Cobb, 1920 and L. filicaudata Ward, 1974; in combination with the tail length and the relative length of the anterior and cephalic setae this defines the species. Laimella tongyeongensis sp. nov. is defined by a combination of characters, principally the de Man's ratios a, b, c and c', the oesophageal bulb length and with regards to the length ratio between the anterior and posterior cephalic setae. Cervonema pseudodeltensis sp. nov. is the only species of the genus so far described which appears to have the anterior cephalic setae marginally longer than the posterior cephalic setae. It is also defined by the amphid position and the relative size of the oesophageal bulb. Cervonema sp. A , described only as females, is defined by the total body length and the relative length of the oesophagus and tail (de Man’s b and c). Cervonema sp. B, on the other hand, is distinct with respect to the de Man's ratios a and b, the R2:R3 sensilla length ratio, and the amphid directly behind the cephalic setae. It also has not been fully described here owing to the lack of male specimens.